2022
DOI: 10.3390/ijms232314871
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aryl Hydrocarbon Receptor Antagonist HBU651 Ameliorates Peripheral and Hypothalamic Inflammation in High-Fat Diet-Induced Obese Mice

Abstract: Obesity is a chronic peripheral inflammation condition that is strongly correlated with neurodegenerative diseases and associated with exposure to environmental chemicals. The aryl hydrocarbon receptor (AhR) is a ligand-activated nuclear receptor activated by environmental chemical, such as dioxins, and also is a regulator of inflammation through interacting with nuclear factor (NF)-κB. In this study, we evaluated the anti-obesity and anti-inflammatory activity of HBU651, a novel AhR antagonist. In BV2 microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Peripheral tissues, including the liver, have been studied as potential sources of biomarkers or insights into PD with the idea that changes in peripheral tissues may reflect systemic alterations associated with PD. We have reported that the mRNA levels of antioxidative enzymes and cytokines in the liver can reflect the systemic status of oxidative stress and inflammation in the mouse model [44]. In this study, we used the liver mRNA levels of inflammatory cytokines as an indirect indicator of systemic inflammation because serum inflammatory cytokine levels were changed similarly to hepatic cytokines [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral tissues, including the liver, have been studied as potential sources of biomarkers or insights into PD with the idea that changes in peripheral tissues may reflect systemic alterations associated with PD. We have reported that the mRNA levels of antioxidative enzymes and cytokines in the liver can reflect the systemic status of oxidative stress and inflammation in the mouse model [44]. In this study, we used the liver mRNA levels of inflammatory cytokines as an indirect indicator of systemic inflammation because serum inflammatory cytokine levels were changed similarly to hepatic cytokines [44].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that the mRNA levels of antioxidative enzymes and cytokines in the liver can reflect the systemic status of oxidative stress and inflammation in the mouse model [44]. In this study, we used the liver mRNA levels of inflammatory cytokines as an indirect indicator of systemic inflammation because serum inflammatory cytokine levels were changed similarly to hepatic cytokines [44]. However, the relationship between liver and brain tissues in terms of the mRNA expression of specific genes in PD is complex and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…HBU651 is a novel synthetic AhR antagonist developed primarily for cancer which appears to be a suitable candidate for SCZ [213].…”
Section: Synthetic Ahr Antagonistsmentioning
confidence: 99%
“…Recombinant interleukin-22 (IL-22) is a pleiotropic cytokine known for facilitating tissue regeneration and protecting the GI tract barrier. Recombinant IL-22, comprising two molecules connected by a fusion protein, exerts better efficacy with reduced systemic side effects [ 223 ].…”
Section: Recombinant Interleukin-22mentioning
confidence: 99%